Resposta :
Explicação passo-a-passo:
f(x) = 3x^2 + x - 1
a) f(0) = 0 + 0 - 1 = -1
b) f(-4) = 48 - 4 - 1 = 43
Resposta:
[tex]\sf f(x) = - 3 x^{2} + x - 1[/tex]
a)
para x = 0 temos:
[tex]\sf f(x) = - 3 x^{2} + x - 1[/tex]
[tex]\sf f(0) = - 3 \cdot 0^{2} + 0 - 1[/tex]
[tex]\sf f(0) = - 3 \cdot 0 - 1[/tex]
[tex]\sf f(0) = 0 - 1[/tex]
[tex]\boxed {\boxed{ \boxed { \boldsymbol{ \sf \displaystyle f(0) = -\: 1 }}}} \quad \gets \mathbf{ Resposta }[/tex]
b)
para x = - 4 temos:
[tex]\sf f(x) = - 3 x^{2} + x - 1[/tex]
[tex]\sf f(-\:4) = - 3 \cdot (-4)^{2} + (-4) - 1[/tex]
[tex]\sf f(-\:4) = - 3 \cdot 16 - 4 - 1[/tex]
[tex]\sf f(-\:4) = - 48 - 5[/tex]
[tex]\boxed {\boxed{ \boxed { \boldsymbol{ \sf \displaystyle f(-\: 4) = -\: 53 }}}} \quad \gets \mathbf{ Resposta }[/tex]
Explicação passo-a-passo: